Frequency and factors associated of potential zoonotic pathogens (Borrelia spp., Rickettsia spp., Leishmania spp., and Anaplasma phagocytophilum) in equids in the state of Bahia, Brazil - Costa, Sonia Carmen Lopo; de Souza Freitas, Jéssica; Carvalho, Fábio Santos; Pereira, Maria Julia Salim; Cordeiro, Matheus Dias; da Fonseca, Adivaldo Henrique; Gomes Jusi, Márcia Mariza [UNESP]; Machado, Rosangela Zacarias [UNESP]; Munhoz, Alexandre Dias (Springer Nature, 2021)
Background: Currently, various zoonotic diseases are classified as emerging or reemerging. Because equids have a direct relationship with various vectors, they are possibly more frequently exposed to zoonotic agents than are humans. The undeniable importance of diseases such as human granulocytic anaplasmosis, spotted fever, and leishmaniasis for both public and animal health, as well as the possibility of equids acting as sources, reservoirs, or even sentinels for these pathogens, justifies the detection of their frequency and factors associated with infection in equids from northeastern Brazil. Methods: Blood samples were collected from 569 equids (528 horses, 33 donkeys, and 8 mules), 516 from a rural area and 53 from an urban area. Pathogen detection was carried out as follows: Borrelia spp. and Rickettsia spp., serological analysis; Leishmania spp., serological analysis and polymerase chain reaction (PCR); Anaplasma phagocytophilum, PCR. Determination of associated factors was carried out through generalized linear models. Results: The frequencies of positivity for the pathogens observed in equids were as follows: Borrelia spp., 13.9% (79/569); Leishmania spp., 3.5% (20/569); Rickettsia spp. 33.4% (190/569). Regarding factors associated with infection, male sex was associated with protection against Borrelia spp.; donkeys and mules were associated with protection against Rickettsia spp., while a younger age was a risk factor. The infection of A. phagocytophilum was not detected in the sampled population. Co-infection was detected in 5.1% (29/569) of the animals. Conclusions: Most of the studied pathogenic agents are present in the prospected area, indicating a possible risk for both human and animal health. This demonstrates that equids can be considered important sentinels in the assessment of pathogens with zoonotic potential in the region. [Figure not available: see fulltext.]
Keywords: Donkeys; Horses; Leishmaniasis; Lyme disease; Mules; Spotted fever; Zoonoses